Barriers and Employment Opportunities for Persons with Disabilities in the Province of Laguna: Heightened Implementation of Republic Act No. 10524 - Anthony P. Rebenque; Chester Alexis C. Buama; Desiree L. Wagan; Marie Ann S. Gonzales; Regina E. Gloria; Bayani A. Guia (Research Synergy Foundation Press, 2026)
This study investigates the barriers and employment opportunities for PWDs in Laguna, a decade after the implementation of R.A. No. 10524, which mandates that government organizations reserve at least 1% of their total positions for PWDs. However, despite the legal framework, many challenges persist in the employment sector for PWDs. The aim is to understand the current situation and identify areas for improvement to promote a more inclusive work environment. The objectives include measuring the perceived level of barriers and the perceived level of employment opportunities across several job categories, with an emphasis on the public sector; examining the relationship between demographic factors and the barriers they encounter; and examining the relationship between barriers and employment opportunities for PWDs across various job categories, including promotion opportunities. This research employed a descriptive-correlational design and administered a survey to 84 respondents. The survey assessed the perceived physical, social, and attitudinal barriers, as well as employment opportunities, in managerial, professional, clerical, technical, service, sales, and elementary roles. Statistical treatment included Pearson correlations to assess relationships among demographics, perceived job opportunities, barriers, and employment opportunities. The study registered a strong positive correlation between perceived physical and social barriers and promotion opportunities. Furthermore, a significant moderate positive correlation was also found between attitudinal barriers and opportunities for promotion. It is therefore concluded that demographic factors do not significantly affect employment opportunities for PWDs; by contrast, physical, social, and attitudinal barriers significantly influence their perceptions of promotion opportunities.